2022
DOI: 10.1108/ohi-07-2021-0147
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based identity in a BIM environment: an architect's perceptions and experiences

Abstract: PurposeInterpreting the meaning structure of architects' actions, behaviours and performances enacted in a building information modelling (BIM) environment is implausible by returning to the classic and ideal imagery of an architect as a natural leader. Yet, little has been empirically explored on how architects perceive their identity and most critically, how they act, behave and perform their way into it in such an environment. Consequently, architects' failing to adapt their core identity to the varying cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…This finding is consistent with Ibrahim et al (2019), who found that 70.4% of local construction players in Malaysia have struggled to understand the actual processes of BIM. In this regard, Shahruddin et al (2022) argued that individuals working in a BIM environment must show their strong analytical skills when working in a collaborative culture. Such a capability would be necessary to improve their performances when leveraging their expertise, particularly during the initial stage.…”
Section: Results and Findingsmentioning
confidence: 99%
“…This finding is consistent with Ibrahim et al (2019), who found that 70.4% of local construction players in Malaysia have struggled to understand the actual processes of BIM. In this regard, Shahruddin et al (2022) argued that individuals working in a BIM environment must show their strong analytical skills when working in a collaborative culture. Such a capability would be necessary to improve their performances when leveraging their expertise, particularly during the initial stage.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Studies have also been conducted to investigate the critical success factors of BIM implementation and adoption (Tsai et al, 2014;Morlhon et al, 2014;Ozorhon and Karahan, 2016;Antwi-Afari et al, 2018;Amuda-Yusuf, 2018;Olawumi and Chan, 2018;Chan et al, 2019b;Dao et al, 2021), critical risk factors (Chien et al, 2014;Khoshfetrat et al, 2020), and drivers (Olanrewaju et al, 2021) related to the use of BIM/BIM implementation in developed countries. Shahruddin et al (2022) interpreted the meaning structure of architects' actions, behaviours, and performances in a building information modelling (BIM) environment. Elgewely et al (2021) proposed a virtual reality (VR) platform for construction detailing that provides experiential learning in a zero-risk environment.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…, 2021) related to the use of BIM/BIM implementation in developed countries. Shahruddin et al. (2022) interpreted the meaning structure of architects' actions, behaviours, and performances in a building information modelling (BIM) environment.…”
Section: Research Background and Gaps In Literaturementioning
confidence: 99%
See 2 more Smart Citations